(3QSGdI aj GdGSJYGfI HGdCfHjGA Ch GdChdjGA GdUGdMjf aj JaQL GdcQhHs
(3ChdgG (B:s
(3GdeSFdI GdChdi eG bhdc ajef OYGFjkG Ch djkG hEKZGJ Hg ai JaQjL GdcQHGJ s
(3BNQgG (B:s
(3ceG jYad YfO Gdedhc Cfg cGaQ eTQc MdGd GdeGd hGdOe hRYe Cfg eSde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGOS YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3GdEeHQhRjGfG (B(404 d) s
Keywords: (3GdJhMjO hGdedd hGdfMds